ENHANCING SPOKEN ENGLISH PERFORMANCE THROUGH TEXT READING: EFL STUDENTS' PERCEPTIONS OF RUBRIC-BASED SELF-ASSESSMENT - Bintang Di Langit Biru; Hendi Pratama (Universitas PGRI Palembang, 2026)
Spoken English proficiency is a fundamental component of communication in English as a Foreign Language (EFL) contexts; however, many learners struggle with speaking anxiety and limited awareness of their own progress. This study investigated EFL students’ perceptions of rubric-based self-assessment as a strategy for improving spoken English performance. Employing a qualitative descriptive approach, the research involved ten eleventh-grade students at SMAN 12 Semarang, Indonesia. The study was conducted over five days, beginning with a text-reading activity on Day 1, followed by three consecutive days of short speaking tasks during which participants recorded their performances and assessed their fluency, pronunciation, and intonation using an analytic rubric. The process concluded with a final text-reading task on Day 5. Data were gathered through self-assessment rubrics, researcher observation notes, and semi-structured interviews to explore students’ experiences, perceived challenges, and observed improvements. The data were analyzed thematically through processes of data condensation, data display, and conclusion drawing. The findings provide valuable insights into the effectiveness of rubric-guided self-reflection in enhancing learners’ awareness of their speaking abilities, addressing challenges in self-evaluation, and fostering greater learner autonomy in EFL speaking classrooms.